2017
DOI: 10.1016/j.celrep.2017.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Suppressor Functions of the Carcinoma Oncogene FOXQ1

Abstract: SUMMARY Opposite lineage-specific regulation of tumor progression by the same transcription factor is an understudied phenomenon. Here, we report that levels of a carcinoma oncogenic transcription factor FOXQ1 are decreased during melanoma progression. Moreover, in melanoma cells, FOXQ1 suppresses the same processes it activates in carcinoma cells: epithelial-to-mesenchymal transition, invasion, and metastasis. We identify that lineage-specific tumor suppressor or oncogenic functions of FOXQ1 in large part dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
1
27
1
Order By: Relevance
“…In contrast, we observed residual pathway activation by FOXB2 in β-catenin–deficient cells. Some FOX proteins, e.g., FOXQ1 and FOXM1, control β-catenin activity via direct association (20, 22). However, FOXB2 did not bind β-catenin or colocalize with nuclear β-catenin ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we observed residual pathway activation by FOXB2 in β-catenin–deficient cells. Some FOX proteins, e.g., FOXQ1 and FOXM1, control β-catenin activity via direct association (20, 22). However, FOXB2 did not bind β-catenin or colocalize with nuclear β-catenin ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among other miR-204-5p target genes, CDH2 and FOXC1 should also be under consideration. CDH2 is a gene that codes N-cadherin, which is broadly expressed in melanoma cells, serving as a promotor of melanoma cell invasion and metastasis via triggering several signaling cascades and transcription factors ( 39 ). N-cadherin-overexpressing melanoma cells lose contacts with neighboring keratinocytes and demonstrate increased adhesion and motility features ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, albeit FOXQ1 is in general considered as an oncoprotein, a recent study demonstrated that FOXQ1 can also act as a tumor suppressor in melanomas (106). It is possible that the same holds true for prostate cancer, as it was found that FOXQ1 was downregulated in prostate tumors, and this downregulation was even accentuated upon metastasis (Fig.…”
Section: Discussionmentioning
confidence: 93%